Management and Governance in Higher Education: South African Universities under Siege - Wolhuter, C.C.; Langa, P. (Acta Paedagogica Vilnensia, 2021)
The recent spate of changes in university management worldwide should be carefully considered, interrogated and assessed against its impact on the capacity of the university fulfilling its unique role in society. For various justifiable reasons, South African higher education has been finding itself under the spotlight of the international community since 1994. The article surveys the South African academic profession vis à vis the changes that have been taking place regarding university governance and management. It is concluded that the South African academic profession, as far as (de jure and de facto) governance and management are concerned, find themselves sandwiched between two forces: from national and institutional governance on top, and the student corps from the bottom. This threatens the very survival of the university. A new exercise surveying the South African academic profession, as provided for by the Academic Profession in Knowledge Society (APIKS) international survey of the academic profession currently taking place, appears both timous and promising.
Keywords: Academic Profession; Higher Education; Managerialism; Student Activism; South Africa